Renal Involvement and HBV Infection Are Common in Chinese Patients With Cryoglobulinemia - Bai, Wei; Zhang, Lixia; Zhao, Jiuliang; Zhang, Shangzhu; Zhou, Jiaxin; Leng, Xiaomei; Liu, Zhengyin; Ye, Wenling; Han, Bing; Tian, Xinping; Li, Mengtao; Zhao, Yan; et al. (Frontiers in Immunology, 2021)
Objectives: This study aimed to describe the main characteristics of Chinese patients with cryoglobulinemia, especially the characteristics of patients with different causes of cryoglobulinemia. Methods: Eighty inpatients diagnosed with cryoglobulinemia from different wards in Peking Union Medical College Hospital were included in this study. Demographic, clinical, biological, and renal pathological data were collected. We analyzed the characteristics of 61 patients with different causes of cryoglobulinemia. Results: Most patients (36/80, 45%) were diagnosed between 40 and 60 years of age. The male: female ratio was 1:1.5. Mixed (II + III) cryoglobulinemia accounted for the majority (43.8%) of cases. Renal involvement (87.5%), cutaneous involvement (57.5%), and fever (27.5%) were the most common clinical manifestations, while other manifestations included serositis and pulmonary and gastrointestinal involvement. The most common renal histopathological pattern was membranoproliferative glomerulonephritis (25/42, 59.5%). The secondary causes of cryoglobulinemia included infectious diseases (26/61, 32.5%), such as hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, and connective tissue diseases (22/61, 27.5%), such as lupus and hematologic tumors (13/61, 16.3%). Patients with hematologic tumors were diagnosed at an older age (P=0.044) and mostly had type I cryoglobulinemia (P<0.001). No significant difference in clinical or biological manifestations was found among patients with different causes of cryoglobulinemia. Conclusions: This is the largest cohort of Chinese patients with cryoglobulinemia. We found that renal involvement and HBV infection might be more common in Chinese patients with cryoglobulinemia.